2018
DOI: 10.32448/entupdates.508084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anatomical Variations on Paranasal Sinus CT

Abstract: Objective: The purpose of this study was to analyze and assess the frequency of anatomical variants of the paranasal sinuses as detected by multidetector computed tomography (MDCT) scanning. Methods: 225 patients (122 males, 103 females) in total, with a median age of 28 (range: 15-77) years were included in this retrospective study. Paranasal computed tomography was conducted in all cases. The scans were reviewed to discover the incidence of nasal septal deviation (NSD), variations of the nasal turbinates, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…17 27 28 On the other hand, the predominance of DNS to the right has been reported in Australia, Malaysia, Saudi Arabia, Turkey, and India. 5 7 9 16 23 29 30 31 Deviation to the right was equal to DNS to the left among Indian subjects. 3…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…17 27 28 On the other hand, the predominance of DNS to the right has been reported in Australia, Malaysia, Saudi Arabia, Turkey, and India. 5 7 9 16 23 29 30 31 Deviation to the right was equal to DNS to the left among Indian subjects. 3…”
Section: Discussionmentioning
confidence: 86%
“…Wide ranges of 55.1 to 89.7% and of 45 to 90.4% were documented in Turkey and Iran, respectively, and these may suggest possible differences within a population group. 12,[21][22][23] Studies performed in Oman and Iraq reported a prevalence of 80 and 72%, respectively. 20,24 Among Australians, Earwaker 5 reported a prevalence of 44%, while the Variations of the Nasal Septum of Adult Nigerians Ominde et al 243 majority of the American population possessed this variant (98.4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation